2022
DOI: 10.1128/spectrum.00997-22
|View full text |Cite
|
Sign up to set email alerts
|

Novel Organization of the Staphylococcal Cassette Chromosome mec Composite Island in Clinical Staphylococcus haemolyticus and Staphylococcus hominis Subspecies hominis Isolates from Dogs

Abstract: In Thailand, the staphylococcal cassette chromosome mec (SCC mec ) element, which causes methicillin resistance through acquisition of the mec gene, has been studied in clinical coagulase-negative Staphylococcus isolates from various companion animals, and Staphylococcus haemolyticus and Staphylococcus hominis subsp. hominis were found to have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A previous study had reported that 15 % (5/34 isolates) of S. hominis clinical isolates harbored SCCmec type VIII(4A), although that study had derived its conclusion from the PCR results of certain conserved regions of the SCCmec element [6]. A more recent study of S. hominis and S. haemolyticus isolates from dogs showed the presence of novel SCCmec composite islands, all of which were initially categorized as non-typeable SCCmec (NT-SCCmec) [28].…”
Section: Prediction Of Antimicrobial Resistance and Virulence Genes F...mentioning
confidence: 99%
“…A previous study had reported that 15 % (5/34 isolates) of S. hominis clinical isolates harbored SCCmec type VIII(4A), although that study had derived its conclusion from the PCR results of certain conserved regions of the SCCmec element [6]. A more recent study of S. hominis and S. haemolyticus isolates from dogs showed the presence of novel SCCmec composite islands, all of which were initially categorized as non-typeable SCCmec (NT-SCCmec) [28].…”
Section: Prediction Of Antimicrobial Resistance and Virulence Genes F...mentioning
confidence: 99%